Pengaruh Kecerdasan Emosional dan Komunikasi Interpersonal Terhadap Hasil Belajar Siswa pada Mata Pelajaran Pengelolaan Bisnis Ritel - Hafizah Yusrida; Tri Kurniawati (Universitas Negeri Padang, 2021)
This study aims to analyze: 1) the effect of emotional quotientand interpersonal communication on student learning outcomes, 2) the effect of emotional quotient on student learning outcomes,3) the effect of interpersonal communicationon student learning outcomes. This is a descriptive and associative research. The sampling technique used is total sampling, with 84 samples.The results show that (1) there is a positive and significant influence of emotional quotient and interpersonal communication on student learning outcomes, (2) there is a positive and significant influence of emotional quotient on student learning outcomes,(3) there is a positive and significant influence of interpersonal communication on student learning outcome.The teacher can always help students control emotions in the classroom and can teach how to communicate well between fellow students in the classroom, because with emotional intelligence and good interpersonal communication will improve student learning outcomes. Keywords: emotional quotient, interpersonal communication, student learning outcomes